Assessment of Polyethylene Terephthalate Waste Carbon and Periwinkle Shells-Based Chitosan as Adsorbent for Trichloroacetic Acid removal from Water. - ABIOYE Babasanmi Oluwole (Institute of Environmental Control Management, Obafemi Awolowo University., 2024)
xxii, 181p